The concentration of maternal sacubitril/valsartan transferred into human milk is negligible - Sirin Falconi; Abiodun Okimi; Shaun Wesley; Pooja Sethi; Palika Datta; Kaytlin Krutsch (Frontiers Media S.A., 2024)
BackgroundPeripartum cardiomyopathy (PPCM) is a common cause of heart failure (HF) in the peripartum. Some medications are considered safe while breastfeeding. However, sacubitril/valsartan (Entresto), while efficacious, is not recommended in breastfeeding women due to concerns about adverse infant development, and no published data suggest otherwise.ObjectivesThis study aimed to assess the transfer of sacubitril/valsartan into human milk and evaluate the infant's risk of drug exposure.MethodsThe InfantRisk Human Milk Biorepository released samples and corresponding health information from five breastfeeding maternal-infant dyads exposed to sacubitril/valsartan. Sacubitril, valsartan, and LBQ657 (sacubitril active metabolite) concentrations were determined using liquid chromatography-mass spectrometry (LC/MS/MS) from timed samples 0, 1, 2, 4, 6, 8, 10, and 12 h following medication administration at steady state conditions.ResultsValsartan levels were below the detection limit of 0.19 ng/mL in all milk samples. Sacubitril was measurable in all milk samples of the five participants, peaking 1 h after drug administration at a mean concentration of 1.52 ng/mL for a total infant dose of 0.00049 mg/kg/12 h and a relative infant dose (RID) calculated at 0.01%. The maximum concentration of its active metabolite LBQ657 in the milk samples was observed 4 h after medication administration and declined over the remaining 12-h dosing interval, for an average concentration of 9.5 ng/mL. The total infant dose was 0.00071 mg/kg/12 h, and the RID was 0.22%. Two mothers reported continuing to breastfeed while taking sacubitril/valsartan; both mothers stated observing no negative effects in their breastfed infants.ConclusionThe transfer of sacubitril/valsartan into human milk is minimal. These concentrations are unlikely to pose a significant risk to breastfeeding infants, with a combined calculated RID of <0.25%, which is far lower than the industry safety standards (RID <10%).